Efecto del enalapril sobre la remodelación cardiaca inducida en ratas hipertensas - Malca Atoche, Joel Cristian (2015)
The HTN is the main cause of morbidity and mortality in adults over 50 years, being the most prevalent modifiable cardiovascular risk factor in the world. At the heart produces a process known as cardiac remodeling, including left ventricular hypertrophy and ventricular fibrosis, antihypertensive treatment being the cornerstone to prevent and/or reduce this process, including ACE inhibitors, as enalapril, which is a main drugs used in our country. OBJECTIVE:To identify the effect of enalapril on cardiac remodeling induced hypertensive rats. MATERIALS AND METHODS: Experimental design simple randomized three groups (21 rats): Control (n = 7), L-NAME (n = 7), L-NAME + enalapril (n = 7). In the two latter groups was administered L-NAME (40 mg / kg / day), a drug that produces persistent hypertension and changes in arterial and cardiac levels. The last group was given enalapril (10 mg / kg / day) for 5 weeks. At the end of the experiment the animals were sacrificed, the hearts was removed, which were measured, weighed, and processed for microscopic study. RESULTS: The L-NAME group showed more intense structural changes compared to the other two groups (p<0.05). While treatment with L-NAME + Enalapril attenuated its effects by inhibiting the IMV, the geometric remodeling of the ventricle, the cross sectional area of cardiac myocytes, interstitial fibrosis and perivascular ventricular. The latter two had statistical difference with controls (p <0.05). CONCLUSION: Treatment with enalapril attenuated structural changes of cardiac remodeling in this experimental model of hypertension